Causes and Flock Level Risk Factors of Sheep and Goat Abortion in Three Agroecology Zones in Ethiopia - Alemayehu, Gezahegn; Mamo, Gezahegne; Alemu, Biruk; Desta, Hiwot; Tadesse, Biniam; Benti, Teferi; Bahiru, Adane; Yimana, Muhabaw; Wieland, Barbara (Frontiers in Veterinary Science, 2021)
A cross-sectional survey was conducted to estimate the incidence of small ruminant abortion and identify its major causes and potential risk factors in goat and sheep flocks in three agroecology and production systems of Ethiopia. Information on pregnancy outcomes and management risk factors were collected for 299 goat and 242 sheep flocks. Blood samples were collected from 133 sheep and 90 goat flocks and tested for Coxiella burnetii, Brucella spp., Chlamydia abortus, and Toxoplasma gondii. A causal diagram outlined relationships between potential predictor variables and abortion in the flock. The effect of management and exposure to infectious causes on the number of abortions in the flock across agroecology was tested using zero-inflated negative binomial regression. Results showed that 142 (58.68%) goats and 53 (17.73%) sheep flocks reported abortions in the 12 months before the survey. The mean annual flock abortion percentages were 16.1% (±26.23) for does and 12.6% (±23.5) for ewes. Farmers perceived infectious diseases, extreme weather conditions, feed shortage, physical traumas, and plant poisoning as the most important causes of abortion. A higher proportion of abortion was recorded during the short rainy season (March to May) and start of the short dry and cold season (June to August) in the lowland mixed crop-livestock and pastoral agroecology and production system, respectively. Overall, 65.41% sheep and 92.22% goat flocks tested positive for one or more abortion causing agents, namely, C. burnetti, C. abortus, Brucella spp., and T. gondii; mixed infection was found in 31.58% sheep and 63.33% goat flocks. Spending the night in a traditional house and providing supplementary feed for pregnant dams were important management factors which significantly (p ≤ 0.05) decreased the risk of abortion by 2.63 and 4.55 times, respectively. However, the presence of other livestock species and dogs in the household and exposure of the flock to Brucella spp. or anyone of the four tested infectious agents significantly (p ≤ 0.05) increased the risk of abortion in sheep and goat flocks. In general, abortion is a challenge for small ruminant production in the study area especially in lowland agroecology and calls for improvement in husbandry practices, health care and biosecurity practices.